O PRODUTOR-ARTISTA E A CIBERCULTURA:uma reflexão sobre a produção musical na era das redes sociais virtuais - FERREIRA, Marcos Ramon Gomes (2011)
Analysis of musical production and its dissemination strategies from the use of social networking. The proposal is to investigate the actions of artists-producers that are within the scope of cyberculture. For this, I analyze relevant concepts to cyberspace and its relationship with the music produced from the use of digital technology. I also investigate the issue of consumption and identities on the Internet, in search of a mapping of the interests that prevail in cyberspace. I define social networks on the internet and point out its essential elements. I use in this research, as a priority, the ethnographic method adapted to the online environment, together with the analysis of social networks. Investigate and analyze the speeches of musicians who have appropriated, in the course of their work with music, the particular circumstances of digital technology and the online environment as a way of acting. Evaluate the speeches and try to draw viable conclusions that enable a understanding of the phenomenon of musical production in the Internet age.